Making training stick: a close examination of how trainee readiness, supervisor support, and practice foster transfer in a mobile technology-based training program - Putter, Stefanie E., author; Kraiger, Kurt, advisor; Johnson, Stefanie, advisor; Steger, Michael, committee member; Mumford, Troy, committee member (Colorado State University. Libraries, 2013)
Although today's organizations are investing copious amounts of time, money, and resources on employee learning and development, trainees often fail to apply their learning and skills on the job, bringing into question the true value of organizational training. In an attempt to improve understanding of the key individual and organizational elements that impact training success, this research explored how trainee readiness, supervisor support, and practice foster transfer in a mobile technology-based training program. Data were collected at three different time points (beginning, middle, and end of training) from 201 frontline workers who participated in an innovative, long-term safety training program. Findings revealed significant relationships between three trainee readiness characteristics and post-training outcomes, with post-hoc analyses suggesting that training self-efficacy and motivation to learn were the best predictors of training effectiveness. Unfortunately, results failed to support the expected interaction between supervisor support (operationalized as safety transformational leadership behaviors) and trainee readiness characteristics in boosting training success. However, follow-up tests revealed strong main effects between safety transformational leadership behaviors and post-training outcomes, with the strongest support for two key supervisory behaviors: individualized consideration and contingent reward. Finally, measurement issues prevented the exploration of the role of practice in a real-world, organizational training program. Study implications, limitations, and opportunities for future research on boosting 'training stickiness' are discussed.
Keywords: mobile technology; safety; safety transformational leadership; trainee readiness; training; transfer